ANALISIS BIBLIOGRAFI NASIONAL INDONESIA PERIODE 2009-2010 - Nani Rahayu, Rochani; Tupan, Tupan (BACA: Jurnal Dokumentasi dan Informasi, 2013)
This study aims to determine: 1) The composition of the fields which listed in Indonesian National Bibliography; 2) The types of publications; 3) The cities where the publications issued; 4) The comparison of the books which have an ISBN or not. The method of this study was descriptive. The source of data was Indonesian National Bibliography vol.57 and 58 no. 1,2,3,4 year 2009 and 2010. The data presented in the form of tables and pictures. The study concluded that 1) The most appeared field in Indonesian National Bibliography was social science, i.e. 1,057 titles (22.93%), the second was technology, i.e. 723 titles (15.68%) and the third was religion, i.e. 716 titles (15.53%). 2) The first rank of publications’ type was books, i.e. 3,992 titles (86.59%), the second was compact dics, i.e. 198 titles (4.30%) and the third was cassettes, i.e. 102 titles (2.21%). 3) The highest number of publications was in 2007, i.e. 2,703 titles (58.63%), the second was in 2008, i.e. 1,205 titles and the third was in 2006, i.e. 650 titles (14.10%). 4) The first rank city where the publications issued was Jakarta, i.e. 3,436 titles (81.75%), the second was Yogyakarta, i.e. 553 (13.16%) and the third was Bandung, i.e. 147 titles (3.50%). 5) It found that a total number of 3,223 titles of books have ISBN and 958 books have no ISBN.